A systematic literature review on technology-enabled experience in hotels / Ritu Narang and Ankita Jaiswal - Narang, Ritu; Jaiswal, Ankita (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
This paper provides an updated review of Technology-Enabled Experience in Hotels. For this purpose, it builds on a systematic literature analysis that provides a structured and systematic way to analyze previous contributions. Earlier systematic reviews have either studied the hospitality technology or the conceptualizations, measurement, antecedents, outcomes and application of experiential value. There is hardly any systematic review study available which connects the two topics. This current study follows the guidelines proposed by vomBrocke et al., (2009) in the field of Information Systems (IS) and are now used in this current study. The findings show that research successfully addressed a variety of research gaps. Essential themes in technology-enabled experience in Hotels were research designs, underpinning theories & models, interactive technologies and hotel contexts. However, other research gaps emerged and provide promising directions for future research are also discussed. This systematic literature review provides an up-to-date review of Technology-Enabled Experience in Hotels and an agenda for future research that addresses the nexus of the hotels and elevation of the customer experience through interactive technologies.